Caramel product from glucose as a sustainable and effective flame retardant for silk fabric. (1st September 2020) - Cheng, Xian-Wei; Huang, Yi-Ting; Zhang, Chen; Gu, Wen-Wen; Ma, Yi-Dan; Shi, Feng-Yi; Guan, Jin-Ping
Abstract: This study aimed at the preparation of caramel product by heating glucose at alkaline condition and its application to develop flame retardant silk fabric. Caramel product was employed to silk through a facile exhaustion approach, and the adsorption property, color depth, flame retardancy and washing durability of caramel on silk fabric were investigated. The adsorption of caramel product on silk at acidic condition imparted brown color and good flame retardancy to silk fabric with self-extinguish ability. The modified silk fabric could still pass the vertical flammability measurement after 15 washing cycles, showing good durability to washing. The bubbling property of caramel during heating is responsible for the enhanced flame retardancy of silk as the formed intumescent char layer could protect silk substrates, revealing a condensed charring mechanism for the modified silk fabric. The caramel product modification exerted little adverse impacts on the handle and tensile strength of silk. The flame retardant modification of silk using eco-friendly and sustainable caramel product is a cleaner production approach compared to the synthetically engineered chemicals. Graphical abstract: Image 1 Highlights: Caramel product has been approved and safely used in foods and beverages. Caramel product is prepared by heating glucose in alkaline condition. Caramel product is a green, eco-friendly and sustainable flame retardant. Caramel imparts semi-durable flame retardancy to silk via facile adsorption technique. Caramel product acts as an intumscent charring flame retardant system.